The Communication Of Halal Tourism With Sharia Regulation In Increasing Income And Community Welfare In North Sumatra - Indah Lestari; Syahrul Amsari (Proceeding International Seminar of Islamic Studies, 2019)
This research was conducted to determine the communication concept of halal tourism based on with the Sharia Regulation Concept in increasing income and welfare of the community. The development of industry 4.0 has an impact on halal tourism as a leading sector industry which is implicate other sectors such as the productivity of goods and services by small and medium business, which in turn will increase income and welfare of the community. Communication has been adopted in many tools such as internet applications that are available many products and services, and one of them is information about various halal tourism destinations around the world. North Sumatra has a large potential of flora and fauna, it can attract the national and international tourists, especially those who are Muslim. Over a period of 5 (five) years, Malaysia is a Muslim-majority visiting North Sumatra as a tourist destination of 15,243 people in 2018. In the other hand, majority of non-Muslim religions also open widely opportunities for halal tourism businesses intended to receive Muslim tourists by providing the facilities needed according to Islamic law. In the context of halal tourism is important to have sharia regulation. This research uses the concept of the Qoran, the method of literature, and the study of central and local government policies. The results of this study concluded that if halal tourism is based on with the Sharia Regulation concept applied by the government and the community positively increases the income and welfare of the people of North Sumatra.